Daratumumab Monotherapy for Heavily Pre-treated and Refractory Myeloma: Results from a UK Multicentre Real World Cohort. (March 2023) - Maouche, Nadjoua; Srinivasan, Anandagopal; Leary, Heather; Collings, Freya; Tseu, Bing; Vallance, Grant D; Ramasamy, Karthik; Kothari, Jaimal
Daratumumab is the first anti-CD38 targeting monoclonal antibody approved as monotherapy in multiply relapsed myeloma patients who progressed following prior treatment with proteasome inhibitors (PIs) and immunomodulatory agents (IMiDs). We present real world data on the efficacy of single agent daratumumab in a cohort of 55 multiply relapsed patients treated in the UK. The median age was 72 years, the majority (96%) received ≥ 3 previous lines of treatment; 54.5% were PI-refractory, 76.4% were IMiD-refractory and 47.2% were double refractory; 20% of patients had high-risk (HR) disease. The overall response rate was 49%. After a median follow up of 9.2 months, the median progression-free survival (PFS) for the total cohort was 5.1 months. Patients who achieved a partial response or better (≥PR) demonstrated a significantly longer PFS compared to those with <PR; 9.8 versus 2.7 months, p < 0.001. Double-refractory patients had an inferior PFS compared to single-refractory patients; 2.7 versus 7.4 months, p = 0.084. High-risk disease was associated with significantly shorter PFS compared to standard-risk (SR); 2.3 versus 6.7 months, p = 0.001. The median overall survival (OS) was 15.9 months. Despite a relatively short PFS seen in the double-refractory and high-risk patients; a favourable median overall survival of 12.9 months was achieved in these groups. Patients who achieved ≥PR, those with a previous objective response to PIs or IMiDs and those with SR disease, all benefited from a significantly longer OS which was not reached. A clear benefit in survival is encouraging in this setting of unmet clinical need and limited treatment options.